Renal Function Improvement Following Bilateral Percutaneous Nephrostomy - Leonardo Grevi Tamara; Sakti Ronggowardhana Brodjonegoro; Fateh Jamal Nahdi (Contagion: Scientific Periodical Journal of Public Health and Coastal Health, 2025)
Urinary tract blockages caused by urolithiasis, trauma, and tumours that spread to the kidneys, bladder, cervix, uterus, or colon would harm renal function. Percutaneous nephrostomy (PCN) provides an option if immediate decompression is required. It serves as a temporary diversion before more serious treatment, to reduce symptoms and preserve renal function in unilateral. This research is a retrospective cohort study that involved patients with obstructive uropathy for about 128 samples from 2019 to 2022. This study was conducted in 2023. Renal function recovery was evaluated by comparing creatinine levels in each group of obstruction aetiology in two periods, before and after obstruction (3rd and 7th day after decompression). History of haemodialysis procedure and chronic kidney disease were excluded The results showed that there was a significant decrease in creatinine from baseline to day 7 of all samples (p=0.001). In the cancer group, there is a significant mean difference in baseline creatinine level and creatinine level at day 7 after the procedure (p=0.008; p<0.05). There is no significant renal function improvement in the stone group. PCN in patients with obstructive uropathy has a significant effect on improving renal function, especially in patients with cervix cancer. Keyword: Obstructive Uropathy, Percutaneous Nephrostomy, Renal Function Improvement